Factors Influencing Customer Loyalty in Telecommunication Industry – A Student outlook of Customer Loyalty - A., Viswanathan (2009)
In the telecommunication industry, customer loyalty is the key to the organizations standings in the marketplace. With unified Telco prevailing in Malaysia, customer loyalty is the base for the organizations operating in the service industry (telecommunication). Developing this knowledge, the study focuses on the important factors (quality, price, value, service, satisfaction and Customer Relationship Management Programs) that have significant effects on the customer loyalty for the telecommunication industry of Malaysia. The study will focus towards the student population of Malaysia and their perception towards loyalty for the current telecommunication firms used by the student, also the decisive factors for loyalty would be derived from the results of study conducted from the students. The overall purpose of this research is to develop a conceptual foundation for investigating the customer loyalty for the telecommunication industry, with the use of the concepts of customer satisfaction, pricing and relationship quality. The research involves a critical examination of the satisfaction-loyalty, price loyalty and the development of a more comprehensive view of the customer’s quality, value and service perception with loyalty. A quantitative method with deductive approach is chosen in this research. In order to collect primary data, a self-completed questionnaire is designed and giving to students who are linked with a particular telecommunication agency that serves multiple telecommunication service provider. The SPSS for windows is used to process the primary data. The findings shows that determinants like price, value, loyalty program and satisfaction have a significant effect on customer loyalty as compared to quality with has a very weak fit to customer loyalty as in the students perspective. With the student attitude and behavior fast changing the factors that affects customer loyalty, has been combined to create a customer loyalty model that focus on improving the loyalty factor in amongst student population. This study can serve as a model to be adopted for years to come in the decisive factors for customer loyalty in the telecommunication industry of Malaysia. The variables, specifically pricing, value, service, quality, satisfaction and customer retention programs are in use for years, through various industries. These particular decisive factors will continue to be of use across the telecommunication industry and other service-oriented industry, as efforts are made to measure customer loyalty in a scale that is usable across the Malaysia.